A study on the impact of glycemic status on central corneal thickness and intraocular pressure in diabetic patients attending a tertiary care center in central Kerala - Vaisna Gopi; Jainy J. Emmatty; Lathika Vasu Kamaladevi (Kerala Journal of Ophthalmology)
Purpose: This study aims to evaluate the central corneal thickness (CCT), intraocular pressure (IOP), and glycemic status in uncontrolled diabetic patients at baseline, 1 week, and 12 weeks, and to examine the relationship between changes in CCT and IOP with fluctuations in glycemic status. Methods: Diabetic individuals with hyperglycemia, defined as having postprandial blood sugar (PPBS) levels exceeding 200 mg/dl and glycated hemoglobin (HbA1c) greater than 7%, aged between 18 and 80 years, were enrolled in the study. Glycemic status was evaluated through fasting blood sugar (FBS), PPBS, and HbA1c levels. Participants underwent a comprehensive ocular examination, CCT measurement utilizing Carl Zeiss Spectral Domain Anterior Segment Optical Coherence Tomography (AS-OCT), and IOP measurement using Goldmann Applanation Tonometer. Participants were advised to pursue treatment for glycemic management. Follow-up evaluations were conducted at 1 week and at 12 weeks. Results: The average CCT was 560.9+/−22 µm during the initial visit, 560.7+/−22 µm at 1 week, and 539.0+/−61.1 µm at 12 weeks (p 0.008). The mean IOP was 17.2+/−2.7 mm Hg at the first visit, 17.1+/−2.7 mm Hg at 1 week, and 15.3+/−2.6 mm Hg at 12 weeks (P 0.01). Conclusion: Achieving optimal glycemic control in diabetic patients leads to a significant reduction in CCT and IOP. Stable euglycemia as evidenced by HbA1c at 3 months is a determinant of reliable IOP measurement. Hence we recommend that healthcare providers should look into the glycemic status, specifically HbA1C once in 3 months during glaucoma related decision making in diabetic patients.